1987
DOI: 10.1037/0097-7403.13.4.354
|View full text |Cite
|
Sign up to set email alerts
|

System-specific differences in behavior regulation: Overrunning and underdrinking in molar nondepriving schedules.

Abstract: In two experiments we tested the molar regulation prediction that animals adjust schedule performance to reduce deviations from baseline response totals. Both experiments constrained the baseline drink-burst length under molar nondepriving schedules but allowed rats to continue running without drinking. In Experiment 1, rats were required to run in order to drink. In Experiment 2, water was delivered independently of running by fixed-time (FT) schedules. Under the run-to-drink contingency, rats exceeded their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Thus, after both spouts became freely available during the contingency-paired test session, the rats contradicted the bliss point model by making too many empty licks—the same result seen in Experiment 2—and too few water licks, a significant shortfall not detected in Experiment 2. This shortfall resembled the underdrinking reported by Gawley (1986) for an experiment in which rats ran in an activity wheel for contingent access to water but received free access to water after various portions of the session had elapsed.…”
Section: Resultssupporting
confidence: 61%
“…Thus, after both spouts became freely available during the contingency-paired test session, the rats contradicted the bliss point model by making too many empty licks—the same result seen in Experiment 2—and too few water licks, a significant shortfall not detected in Experiment 2. This shortfall resembled the underdrinking reported by Gawley (1986) for an experiment in which rats ran in an activity wheel for contingent access to water but received free access to water after various portions of the session had elapsed.…”
Section: Resultssupporting
confidence: 61%
“…Franklin and Quartermain (1970) studied rats licking (Experiment 1) or pressing levers (Experiment 2), with water as the reinforcer in both cases. The mean number of licks per 5-min interval remained approximately constant across 20-min sessions, but the number of lever presses increased (see also Gawley, Timberlake, & Lucas, 1987). Different schedules of reinforcement may produce different changes in responding.…”
Section: Positive Reinforcement Schedules Of Reinforcementmentioning
confidence: 89%
“…Other research has indicated complex interactions of schedule constraints with particular instrumental and contingent responses. Gawley et al (1986) and Gawley, Timberlake, & Lucas, (1987) found that slightly disrupting the drinking of rats significantly decreased their baseline intake, whereas forcing rats to markedly alter their pattern and amount of running in order to drink did not affect their free running (see also Tierney, Smith, & Gannon, 1987, and perhaps Allison, Buxton, & Moore, 1987). This is reminiscent of the tendency of Kavanau's (1963) deer mice to work to turn off a wheel that was rotating and turn on a wheel that was locked.…”
Section: Limitations On and Extensions Of The Disequilibrium Approachmentioning
confidence: 99%